PENGARUH KEPEMIMPINAN YANG MELAYANI TERHADAP PERILAKU KERJA INOVATIF DENGAN JOB CRAFTING DAN OTONOMI KERJA SEBAGAI VARIABEL PEMEDIASI (Studi pada Karyawan PT Nelta Multi Gracia) - Novanto Yusuf Triatmoko; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to examine the effect of Servant Leadership on Innovative Work Behavior mediated by Job Crafting and Job Autonomy on employees of PT Nelta Multi Gracia. The saturation sampling method was used to determine the number of research samples, namely all employees of PT Nelta Multi Gracia. The analytical technique used is path analysis with the SPSS:25 program to determine the path coefficient and the effect of the independent variable on the dependent variable. The results showed that Servant Leadership had a positive and significant effect on Innovative Work Behavior. Servant Leadership has a positive and significant effect on Job Crafting. Servant Leadership has a positive and significant effect on Job Autonomy. Job Crafting has a positive and significant effect on Innovative Work Behavior. Job Autonomy has a positive and significant effect on Innovative Work Behavior. This study also shows that Job Crafting and Job Autonomy can mediate the effect of Servant Leadership on Innovative Work Behavior.